(untitled) (Hoboken, NJ., 2006)
Biological monitoring of running waters is a scientifically and economically valid approach for surveys and monitoring programmes to assess the water quality. Biological Monitoring of Rivers is a timely, up-to-date book that includes a good number of practical how-to-do chapters.
Quan trắc chất lượng nước bằng biện pháp sinh học
Keywords: Water quality biological assessment.,Stream ecology,Environmental monitoring